GARNET MINERALIZATION ASSOCIATED WITH LATE MAGMATIC AND HYDROTHERMAL-METASOMATIC PROCESSES IN DUNITES OF THE NIZHNY TAGIL CLINOPYROXENITE-DUNITE MASSIF, CENTRAL URALS - S.Yu. Stepanov; R.S. Palamarchuk; V.V. Shilovskikh; D.A. Artemiev; A.V. Korneev; A.K. Kozin (Минералогия)
The miarolitic dunites of the Nizhny Tagil massif (Central Urals), the structure of miaroles and the principles of co-occurrence of minerals are studied. Garnets from miaroles are characterized in details and are compared with those from chromitites and metasomatites after dunites. The structure of miarolitic dunites and miaroles is described using ontogenic approaches. The structure and composition of garnets are studied by SEM and LA-ICP-MS. Three assemblages of garnets are established in rocks of the Nizhny Tagil massif: Cr-andradite in miarolitic dunites, uvarovite in massive veined chromitites and demantoid in metasomatites after dunites. Garnets from all assemblages belong to the ugrandite group and are characterized by specific features of chemical composition including higher Cr2O3 content. Garnets are also characterized by contrasting concentrations of trace elements, such as V, Mn and Ti, as well as differences in REE pattern. A paragenetic sequence of formation of major rock-forming minerals is suggested for dunites, chromites and metasomatites after dunites of the Nizhny Tagil massif.